Posterolateral fusion in spondylolisthesis of the lumbosacral segment. - Jorge A. Jerez Labrada; Yoan M. Quiñónez González; Ricardo Aguilar González; Francisco J. Lam González; Félix Rodríguez Fernández; Dania Zúñiga Estrada (Medisur, 2006)
Background: Since centuries ago it has been written about lumbar pain, still its treatment remains enigmatic. At present, all developed spinal surgery institutions use the transpedicular fixation methods, but we lack the right technology for what we use the posterolateral fusion. Objetive: to evaluate the results in the aplicate of the posterolateral fusion in spondylolisthesis of the lumbosacral segment. Methods: A Retrospective-descriptive, correlational, and of a series of cases study, carried out in traumatology and orthopaedics service of the Universitarian Provincial Hospital ¨Dr. Gustavo Aldereguía Lima¨ of Cienfuegos, in which were included the 33 patients with spondylisthesis of the lumbosacral segment, who received inter-transversal posterolateral fusion. All the patients got plain anteroposterior and lateral radiography, including right and left slanting sights, to the doubtful cases dynamic sights with flexion and extension of the trunk were applied. To the patients with signs of radicular irritation, a digitalized axial tomography was applied. Results: The main etiological causes in these patients were the isthmic one, followed by degenerative and dysplastic ones. The posterolateral function was carried out alone or combined with other surgical techniques; to the patients with lumbar pain that also had associated signs of radicular irritation were applied exeresis of posterior arch with release of the endangered roots. The more frequent complication was the recurrent pain, present in 6 patients, followed by granuloma of the surgical wound. Conclusions: In spite of lacking a modern instrumentation system, the problem of spondylolisthesis can be solved with only dominating this traditional technique consistent in posterolateral fixation.